Enhancing Startup Business Performance Through Iterative Strategies and Lean Programs: Insights from Capital Cities in Indonesia to Unlock Central Asia’s Potential - Muhammad Fahreza; Dini Turipanam Alamanda; Ubaidillah Zuhdi; Grisna Anggadwita; Dinar Mariam Kurniati; Eddy Soeryanto Soegoto (Australasian Accounting, Business and Finance Journal, 2024)
This study investigates the influence of the startup ecosystem on startup business performance in Capital Cities (Jakarta, Bogor, Depok, Tangerang, and Bekasi), emphasizing the roles of iterative incremental strategies and lean startup programs. This study also examines the similarities between Central Asian countries like Kazakhstan, Uzbekistan, and the Indonesia region. Central Asian countries face unique challenges, including less mature ecosystems, regulatory hurdles, and cultural attitudes toward entrepreneurship. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) on data from startups aged 1-10 years, the research reveals that these strategies significantly mediate the relationship between ecosystem support and startup success, enhancing market optimization, innovation, and sustainability. Startups achieve better financial and nonfinancial outcomes by effectively leveraging ecosystem structures through agile methodologies. By drawing on capital city experiences, Central Asian policymakers can improve startup environments through robust support structures, regulatory clarity, and education on agile methodologies. This research offers a model for enhancing startup business performance via ecosystem support and strategic agility, informing policy and program development in other regions.
Keywords: Startup Ecosystem; Lean Startup Programs; Iterative Strategies; Startup Business Performance